2012
DOI: 10.1242/dev.066647
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor acts as a neurotrophin in the developing inner ear

Abstract: This study is the first to demonstrate that macrophage migration inhibitory factor (MIF), an immune system ‘inflammatory’ cytokine that is released by the developing otocyst, plays a role in regulating early innervation of the mouse and chick inner ear. We demonstrate that MIF is a major bioactive component of the previously uncharacterized otocyst-derived factor, which directs initial neurite outgrowth from the statoacoustic ganglion (SAG) to the developing inner ear. Recombinant MIF acts as a neurotrophin in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 47 publications
5
56
0
Order By: Relevance
“…Several highly conserved families of axon guidance molecules and their receptors are present during this pathfinding phase, including Ephs/ephrins (Siddiqui and Cramer, 2005), Semaphorins (Chilton and Guthrie, 2003), and Slits/Robos (Holmes and Niswander, 2001; Battisti and Fekete, 2008; Wang et al, 2013). Molecules that can influence otic axon outgrowth include neurotrophins (Tessarollo et al, 2004; Fritzsch et al, 2005), inflammatory cytokines (Bianchi et al, 2005; Banks et al, 2012), ephrins (Bianchi and Gray, 2002; Brors et al, 2003; Zhou et al, 2011; Coate et al, 2012), Semaphorins (Gu et al, 2003; Fantetti et al, 2011) and members of the BMP, Shh, and FGF morphogen families (Hossain et al, 1996; Hossain and Morest, 2000; Hossain et al, 2008; Fantetti and Fekete, 2012). Peripheral otic axon pathfinding has been the subject of recent reviews (Pauley et al, 2005; Webber and Raz, 2006; Fekete and Campero, 2007; Appler and Goodrich, 2011; Coate and Kelly, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Several highly conserved families of axon guidance molecules and their receptors are present during this pathfinding phase, including Ephs/ephrins (Siddiqui and Cramer, 2005), Semaphorins (Chilton and Guthrie, 2003), and Slits/Robos (Holmes and Niswander, 2001; Battisti and Fekete, 2008; Wang et al, 2013). Molecules that can influence otic axon outgrowth include neurotrophins (Tessarollo et al, 2004; Fritzsch et al, 2005), inflammatory cytokines (Bianchi et al, 2005; Banks et al, 2012), ephrins (Bianchi and Gray, 2002; Brors et al, 2003; Zhou et al, 2011; Coate et al, 2012), Semaphorins (Gu et al, 2003; Fantetti et al, 2011) and members of the BMP, Shh, and FGF morphogen families (Hossain et al, 1996; Hossain and Morest, 2000; Hossain et al, 2008; Fantetti and Fekete, 2012). Peripheral otic axon pathfinding has been the subject of recent reviews (Pauley et al, 2005; Webber and Raz, 2006; Fekete and Campero, 2007; Appler and Goodrich, 2011; Coate and Kelly, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies highlighted that a CD40‐ and CD45‐deficiency may positively influence neuronal survival (Bak, Kim, Kim, & Choi, ; Carson, Thrash, & Walter, ; Giunta, Figueroa, Town, & Tan, ; Keilhoff, Schweizer, John, Langnaese, & Ebmeyer, ; Koshimizu et al, ; Michael, Gbolahan, Ansa, Abdulbasitand, & Azeez, ; Town, Tan, & Mullan, ). Encoded protein of CD74 plays an important role in the induction of selective pro‐inflammatory molecules (Bank et al, ; Beswick & Reyes, ). In addition, a low level of the CD14 gene, which is known to act as a co‐receptor for the endotoxin lipopolysaccharide (LPS), has been found to ameliorate inflammatory responses, thus suggesting a role in conserving life‐maintaining signals (Bate & Williams, ; Bate, Veerhuis, Eikelenboom, & Williams, ; Butovsky et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Another reason an inner ear phenotype has not been characterized is that significant numbers of mutants die, either during embryonic stages (all Zic2 Ku/Ku , ~24% of Zic3 Bn ) or shortly after birth (50% of Zic1 −/− , all Zic2 kd/kd , some Zic5 −/− ) (Aruga et al, 1998; Klootwijk et al, 2000; Nagai et al, 2000; Elms et al, 2003; Inoue et al, 2004), making it impossible to detect signs of inner ear defects that affect the mature function of this sensory organ, such as changes in gait or posture, abnormal behaviors such as circling, and changes in the acoustic startle response or auditory brainstem responses (ABR) (Saul et al, 2008). Studies using these mice, including recording of ABRs in any animals, including heterozygotes, that live to postnatal stages, as we have done for other mouse mutations (Bank et al, 2012) could provide insights into how individual Zic genes function during inner ear development. Further, the generation of compound Zic mutants would be useful to address questions of redundancy among the Zic genes during inner ear development, as we have shown that the Zic genes are expressed in overlapping regions of the periotic mesenchyme in both chick and mouse.…”
Section: Discussionmentioning
confidence: 99%